Effect of Low-protein Diet on Haemato-biochemical Parameters and Carcass Traits of Japanese Quails (Coturnix coturnix japonica) Raised under Intensive Caged Management - Buragohain, R.; John, Jobin (International Journal of Bio-resource and Stress Management, 2026)
The study, conducted during May-July, 2024 at Department of Animal Nutrition, College of Veterinary Sciences and A.H., CAU (Imphal), Aizawl, Mizoram, assessed effect of low-protein diet on blood haemato-biochemical parameters and carcass traits of Japanese quails. One-day old, 280 quail chicks were randomly distributed into seven homogenous treatments and fed quail starter (up to 3 weeks) and finisher (4 to 6 weeks) rations formulated as per ICAR standard with crude protein level reduced by 0%, 5%, 10%, 15%, 20%, 25% and 30% for treatment 1 to 7, respectively. The rations were isocaloric with other nutrients as per ICAR standard. After 15 days brooding, chicks were reared in cages in well-ventilated house providing feed and water ad libitum. For haemato-biochemical parameters, blood was collected on 21st and 42nd day of age from 4 quails of each treatment. Biochemical parameters were analyzed by analytical kit (Fujifilm) and haematological parameters were estimated in automated haematology analyser. At 6th week, four quails from each treatment were slaughtered for carcass characteristics study. The results revealed non-significant effect of low-protein diets on all the blood haematological and biochemical parameters and values were within normal range. There was no significant effect of reduced protein level on dressing percentage and organ weights of Japanese quails, but weights of breast, legs and wings were significantly (p<0.01) reduced. Considering non-significant effect on overall health and metabolism, reduction of dietary crude protein up to 30% of ICAR standard was recommended for growing Japanese quails under intensive caged management.